Gender Theory and the Catholic Tradition: The Hypostatic Union and Maximus the Confessor - Dawson Vasquez, David ca. 20./21. Jh. (Heythrop journal, 2025)
In this article I argue that the traditional understanding of the humanity and divinity of Jesus (the hypostatic union) provides a basis for contemporary gender theory that current ecclesial critics overlook. Taking my point of departure from a recent suggestion by Adrian Thatcher, I engage the contemporary discussion about gender in Maximus the Confessor in order to highlight and focus on the Christological foundation of the latter's thought. I revisit Maximus's Ambiguum 41, the clearest account of gender in Maximus, showing how recent scholars, such as Skliris, Brown Dewhurst, and Mitralexis, have used this to open the way for a reconsideration of gender distinctions. The question of the interpretation of logos and tropos is crucial here. I then analyse the conclusions of these scholars, charting a middle way between a perceived negation of gender in Maximus and a gender polarity. My argument is that when approached from the perspective of the person of Jesus, Maximus is closer to affirming the contemporary concept of gender fluidity than has sometimes been recognised.